2018
DOI: 10.2147/opth.s188785
|View full text |Cite
|
Sign up to set email alerts
|

The Implantable Collamer Lens with a central port: review of the literature

Abstract: The purpose of this review is to summarize preclinical and clinical data from publications appearing in the peer-reviewed scientific literature relevant to the safety and effectiveness of the EVO Implantable Collamer Lens (ICL) posterior chamber phakic refractive lens with a central port (V4c Visian ICL with KS Aquaport, STAAR Surgical, Inc.). A literature search was conducted using PubMed.gov to identify all articles relating to the EVO ICL. Articles were examined for their relevance, and the references cited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
118
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 63 publications
6
118
1
2
Order By: Relevance
“…However, all these studies evaluated patients implanted with older ICL models. With the present V4c ICL, recent long-term studies [13,14] and meta-analysis reported no postoperative complications [1,2]. Kamiya et al [3] and Takahashi et al [4], in an older patient sample (with 6 months of follow-up) similar to ours, did not report either asymptomatic or symptomatic cataract formation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, all these studies evaluated patients implanted with older ICL models. With the present V4c ICL, recent long-term studies [13,14] and meta-analysis reported no postoperative complications [1,2]. Kamiya et al [3] and Takahashi et al [4], in an older patient sample (with 6 months of follow-up) similar to ours, did not report either asymptomatic or symptomatic cataract formation.…”
Section: Discussionsupporting
confidence: 74%
“…Note also that most eyes had an UDVA of 20/25 or better (>75%, Figure 1(a)). Like the one we have introduced, there are different studies in the literature analysing this lens with short, medium, and long follow-up periods [1,2]. In order to compare our outcomes with those published previously, we have considered for the discussion only those studies reporting data for the V4c ICL model at 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key factor in determining refractive outcome after TICL implantation is postoperative rotational stability. Packer et al [4] reported that 0.33% (10/2970) of patients that underwent V4C implants required a second adjustment surgery and completely achieved the desired results subsequently. Similar occurrence rate (0.32%) was disclosed in retrospective analysis of 310 TICLs implantations in our refractive center since 2014 after one patient with a clear history of trauma was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Serious postoperative complications of ICL implantation, including cataract, pupillary block, or lens dislocation, can occur, but the incidence is low. 2,3 We report the case of spontaneous ICL dislocation and pupillary capture and discuss the possible association with intake of oral antidepressants.…”
Section: Introductionmentioning
confidence: 99%